Reviewing the evidence for shockwave- and cell-based regenerative therapies in the treatment of erectile dysfunction. (March 2021) - Drury, Robert; Natale, Caleb; Hellstrom, Wayne J. G.
Erectile dysfunction (ED) is both a common and complex disease process. Existing ED treatments do not always achieve adequate results. There is clinical interest in employing regenerative therapies, including low-intensity extracorporeal shockwave therapy (Li-ESWT), platelet rich plasma (PRP), and stem cell therapy (SCT), in the treatment of ED as adjunct or alternative treatments. Here, we present evidence for emerging shockwave- and cell-based regenerative therapies for the treatment of ED following a thorough review of the existing PubMed literature pertaining to Li-ESWT, PRP, and SCT in relation to the treatment of ED. Li-ESWT causes microtrauma in tissue that hypothetically upregulates angiogenesis and recruits stem cells. Several large-scale systematic reviews and meta-analyses have reported that Li-ESWT improved ED in humans. Additionally, evidence has commenced to show that Li-ESWT may be effective against two recognized and complex etiologies of ED: diabetic and neurogenic. PRP delivers an autologous sample rich in growth factors to damaged tissue. Animal model studies have demonstrated improved erectile function recovery as well as preservation of cavernous nerve axons. Studies with PRP in humans are limited. SCT utilizes the regenerative potential of stem cells for healing of damaged tissue. In the treatment of ED, SCT has been used in the setting of diabetic and post-prostatectomy ED. Results of human studies are varied, although SCT treatments did result in increased erectile rigidity with some patients recovering the ability to achieve penetration. While these regenerative therapies show potential to augment the current treatment regimen for ED, there is a paucity of evidence to support the safety and efficacy of these treatments. Further research is necessary to define the role of these alternative therapies in the treatment of ED.